Optimisation of Surface Roughness in The Cnc Milling Process - HASSAN, MUHAMMAD SYAZWAN; MOHD AMIN, AZRISZUL (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The main aspect for machining today is to produce and achieve a better surface quality in a short period and with a lower energy consumption. Surface roughness is a common criterion of the quality characteristics for machining processes. In order to increase the consistency of the surface finish, the suitable cutting parameters should be implemented. This thesis aimed to optimise the surface roughness in 3D cutting using CNC end milling machine. The depth of cut, the cutting speed and the feed rate are the parameters used in optimising the surface roughness. The best range of the cutting parameters were obtained by using Design of Experiment (DOE) which is Response Surface Methodology (RSM) method. The RSM method is used because it is one of the most efficient and effective techniques to determine the best combination of parameters. The experiments were run by using the data simulation from Mastercam X7 and all the data command were used in Nexus 410A-II 3-Axis Computer Numerical Method (CNC) machine with the MAZATROL controller. The surface roughness of workpiece is measured using surface roughness tester, Mitutoyo SJ-410. The analysing data are made by employing RSM and ANOVA using Minitab 19 software. The direct effects and interaction effects were graphically plotted which helps to study the significance of these parameters on surface roughness.